PERENCANAAN SALURAN DRAINASE PRIMER DI KAWASAN UNIVERSITAS NEGERI PADANG - Herza, Habil Abdilah; Arbi, Yaumal (Jurnal Applied Science in Civil Engineering, 2024)
Abstract : The primary drainage channel capacity of Universitas Negeri Padang (UNP) proves inadequate for managing the substantial discharge due to sedimentation thickness and the deteriorating functionality of the existing channel. Consequently, this leads to the overflow of the drainage channel, resulting in instances of flooding and standing water. The objective of this research is to analyze and re-plan the primary channel to ensure optimal functionality. In the research methodology, hydrological data is processed using the Log-Pearson II method to derive rainfall intensity values for specific return periods. These values are subsequently simulated using HEC-HMS software to ascertain the design discharge. Hydraulic simulation is then conducted utilizing HEC-RAS software to evaluate the capacity of the existing channel to accommodate the design discharge. Through the processing of hydrological data and simulation employing HEC-HMS, the design discharge for a 100-year return period is determined to be 83 m3/s. The hydraulic simulation utilizing HEC-RAS, incorporating input values of the design discharge and existing channel dimensions, indicates that the existing drainage channel's capacity falls short of the design discharge. This signifies that the current dimensions are insufficient to handle the design discharge, necessitating a redesign of the channel dimensions. The redesigned channel dimensions and simulation outcomes reveal that the planned channel capacity exceeds the planned discharge, indicating that the proposed channel dimensions can effectively accommodate the intended discharge.